Philanthropic conference-based requirements engineering in time of pandemic and beyond - Levy, Meira; Hadar, Irit; Horkoff, Jennifer; Hayes, Jane Huffman; Paech, Barbara; Dekhtyar, Alex; Mussbacher, Gunter; Paja, Elda; Li, Tong; Lee, Seok Won; Fang, Dongfeng (Requirements Engineering, 2023)
As software engineering (SE) practitioners, we can help society by using our communities of experts to address a software need of a socially conscious organization. Doing so can benefit society in the locale of a SE conference and provide access to international experts for local organizations. Furthermore, established SE researchers as well as practitioners and students have the opportunity for a unique learning experience. While the SE community has already realized the importance of addressing human values and promoting social good objectives in software development, we are unaware of previous attempts to leverage SE conferences for this activity. Conferences present an opportunity to enjoy the assembly of SE practitioners, researchers, and students for the purpose of a philanthropic endeavor. Over the past four years of running a “Requirements Engineering for Social Good” event called RE Cares, co-located with the International Conference on Requirements Engineering, we worked with the stakeholders local to the conference venue. We selected stakeholders who would not necessarily have ready access to requirements engineering, software design, and development expertise otherwise, to build software targeting “good causes.” In the last two years, this event was altered to adapt to the constraints induced by COVID-19, moving to a hybrid mode and changing many of its practices accordingly. This paper summarizes and generalizes our experiences, discussing our lessons learned in the context of the pandemic and beyond and providing a framework for conducting similar social contribution in any SE conferences in general.
Keywords: Engineering community; Engineering practitioners; Human values; Hybrid event; International experts; Learning experiences; Pandemic; Philanthropic project; Requirement engineering; Stakeholder; COVID-19; Hybrid events; Pandemic; Philanthropic projects; Requirements engineering; Stakeholders